UNTERSUCHUNG DER TBERSCHALLSTROMUNG UM STUMPFE KEGEL MIT SCHARFKANTIGER SCHULTER. - Giesbrecht, Hartmut
The axial symmetric supersonic flow about blunted cones with a sharp edge is calculated by means of the inverse blunt-body-method of VAN DYKE. and the method of characteristics. Two nose forms are investigated: A spherical cap and a pointed cone having a 400 semi-angle. The results are compared with schlieren photos and shadowgraphs taken in a ballistic range. The existence of a secondary shock behind the sharp edge is discussed in detail. It is found that the flow outside a layer of increased entropy close to the wall becomes conical again. Whereas the pressure reaches the final value faster at low MACHnumbers, the shock wave gets straight more quickly at higher MACHnumbers. Disturbances at slender cones will still be felt at great distances from the nose.